2003
DOI: 10.1034/j.1600-6143.2003.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Heart Beating Donor Kidneys with Delayed Graft Function Have Superior Graft Survival Compared with Conventional Heart-Beating Donor Kidneys That Develop Delayed Graft Function

Abstract: Delayed graft function may have an association with reduced graft survival, and nonheart-beating donor (NHBD) kidneys have higher rates of delayed graft function (DGF) than heart-beating donor (HBD) kidneys. This study compared outcome of renal transplants from HBDs who developed DGF, with NHBDs who developed DGF.All recipients of HBD and NHBD kidneys who developed DGF were identified during a 10-year period. All patients with graft primary nonfunction were excluded from analysis.Four hundred and fifty-six fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 31 publications
6
66
0
4
Order By: Relevance
“…Compared with HBD kidneys, graft survival of NHBD kidneys with DGF is better (15). DGF in NHBD kidneys is largely affected by the unavoidable warm ischemic renal insult, which may be completely different from the cause of DGF in heart-beating kidneys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with HBD kidneys, graft survival of NHBD kidneys with DGF is better (15). DGF in NHBD kidneys is largely affected by the unavoidable warm ischemic renal insult, which may be completely different from the cause of DGF in heart-beating kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…In renal allografts from heartbeating donors (HBD), DGF is reported as an independent risk factor for reduced long-term graft (8,9) and patient survival (10). Others report no effect on long-term outcome (11,12), although there may be an adverse effect on the long-term renal function if DGF is associated with periods of acute rejection (AR) (14,15). It is also suggested that DGF longer than 3 weeks leads to a higher mortality, while the effect on late graft function is less important (10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HMP permits longer preservation times without significant consequences to the allograft. Current notions suggest that HMP prevents and/or ameliorates injury to the kidney suffered as a result of preagonal hemodynamic and metabolic perturbations to the donor [25,26].…”
Section: Hypothermic Machine Perfusionmentioning
confidence: 99%
“…Finally, delayed graft function is a risk factor for acute rejection and graft loss, although the detrimental effect of delayed graft function on graft survival appears to be much weaker in transplants with DCD donor renal allograft than in transplants with donation after brain death donor renal allografts. 4,5 Consequently, reducing the incidence of delayed graft function after transplant with DCD donor renal allografts would facilitate managing recipients during the first weeks after a transplant and potentially improve long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%